2011
DOI: 10.1016/j.hcl.2011.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Strategies to Enhance Nerve Regeneration in Composite Tissue Allotransplantation

Abstract: Synopsis Reinnervation of a hand transplant ultimately dictates functional recovery but provides a significant regenerative challenge. The authors present a review highlighting interventions to enhance nerve regeneration through acceleration of axonal regeneration or augmentation of Schwann cell supportand discuss their relevance to composite tissue allotransplantation. Surgical techniques that may be performed at the time of transplantation to optimize intrinsic muscle recovery—including appropriate alignment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 109 publications
0
41
0
Order By: Relevance
“…Nerve injury may involve variable lengths of nerve impairment, and the degree of the lesion is affected by the type of lesion [45]. Also, the prognosis is dependent on the age of the patient, location of the lesion-distal fare better than proximal lesions-and also demographics [42].…”
Section: Diagnosismentioning
confidence: 99%
“…Nerve injury may involve variable lengths of nerve impairment, and the degree of the lesion is affected by the type of lesion [45]. Also, the prognosis is dependent on the age of the patient, location of the lesion-distal fare better than proximal lesions-and also demographics [42].…”
Section: Diagnosismentioning
confidence: 99%
“…FK506 is also used as a systemic immunosuppressant to prevent nerve allograft rejection. 66,67 The immunosuppressant was found to have nerve regenerative properties when administered peripherally following injuries to peripheral nerves; subsequently several studies have demonstrated the neuroprotective and neurotrophic effects of Tacrolimus. 69 Despite the promise of this research, well-controlled clinical studies are still necessary to demonstrate the effect of FK506 in nerve regeneration.…”
Section: Fk506 (Tacrolimusmentioning
confidence: 99%
“…91 Another issue more specific to VCA is the possibility that allogeneic Schwann cells in the transplanted nerve may undergo rejection. 67 Therefore, strategies to create an environment of supportive Schwann cells in the distal aspect of the regenerating nerve are of paramount research interest.…”
Section: Stem Cell Biology In Peripheral Nerve Regenerationmentioning
confidence: 99%
“…tacrolimus) could enhance the regeneration of the allografts after HAT. This is based on the hypothesis that tacrolimus increases the pathway of GAP-43 protein thus enhancing axonal regeneration observed in experimental models [26]. Only very recently the clinical effect of tacrolimus on nerve regeneration has been challenged in a phase II clinical trial in five patients receiving tacrolimus after nerve primary suturing or reconstruction using autografts.…”
Section: Metabolicmentioning
confidence: 99%